Effect of Physical Elements in Counseling Room on Women's Psychological Comfort: Pulih Foundation Case Study - Khoizuron Syakira; Dona Saphiranti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The counseling room plays a critical role in supporting psychological recovery, particularly for young adult women in Indonesia who experience a high prevalence of emotional mental disorders such as anxiety and depression. This study aims to examine user perceptions of the physical elements of counseling rooms—specifically lighting, color, and spatial layout—and to identify which components contribute most significantly to psychological comfort. Conducted at the Pulih Foundation Clinic, the research employs a mixed-method case study approach with data collected through structured observation, semi-structured interviews with two psychologists, and a main questionnaire completed by 52 female clients. Instruments used in the survey included the Environmental Satisfaction Questionnaire and the Perceived Restorativeness Scale. The results reveal a clear perceptual dichotomy: while spatial elements such as layout and furniture arrangement were positively perceived, sensory components—particularly lighting and color—received low satisfaction scores and were measured to be below standard comfort levels. The study also highlights the critical importance of acoustic privacy, which received the highest importance score among participants. A strong correlation was found between perceptions of lighting and color, indicating the interdependence of these environmental aspects. Based on these findings, the study recommends targeted design interventions that prioritize the improvement of acoustic insulation and the implementation of adaptive lighting systems. These recommendations aim to support the creation of gender-responsive, psychologically supportive counseling spaces that are attuned to the needs of young adult women in recovery.